2008
DOI: 10.1002/dev.20354
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar modulation of taste aversion learning by the time of day in developing rats

Abstract: The ontogeny of the temporal context modulation of conditioned taste aversion was studied in male Wistar rats using a palatable 1% NaCl solution. A procedure that included two saline preexposures, a single pairing saline-lithium chloride (0.15 M; 1% b.w.) either at the same or a different time of day of preexposures and a one-bottle test at the same time than preexposure was applied. Four age groups (PN32, PN48, PN64, and PN100) covering the complete range from adolescence to the adult period were tested. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 82 publications
0
12
0
2
Order By: Relevance
“…In line with this notion and on the basis of their previous finding that environmental and temporal contexts can modulate taste aversion learning (Moron et al, 2002), Gallo and her colleagues (Manrique et al, 2009a,b) have studied modulation of taste aversion learning by the time of day (morning 9:00 or evening 19:00) in rats of different ages ranging from 32-day-old to 25-month-old and the role of hippocampus in such a modulation. Their results suggest that the ability to form segregated representations of a complex experience is impaired in aging and abolished by lesions of the dorsal hippocampus.…”
Section: Avoidancementioning
confidence: 54%
“…In line with this notion and on the basis of their previous finding that environmental and temporal contexts can modulate taste aversion learning (Moron et al, 2002), Gallo and her colleagues (Manrique et al, 2009a,b) have studied modulation of taste aversion learning by the time of day (morning 9:00 or evening 19:00) in rats of different ages ranging from 32-day-old to 25-month-old and the role of hippocampus in such a modulation. Their results suggest that the ability to form segregated representations of a complex experience is impaired in aging and abolished by lesions of the dorsal hippocampus.…”
Section: Avoidancementioning
confidence: 54%
“…A similar result was reported by the same authors when analyzing the role of context in the renewal effect after extinction of fear memories during this ontogenetic period (Yap & Richardson, 2007). Manrique and collaborators (2009) also reported that the temporal context-dependency of latent inhibition, a hippocampal-dependent phenomenon (Molero, Moron, Angeles Ballesteros, Manrique, Fenton & Gallo, 2005), emerges late in adolescence. What is happening in this developmental stage in response to experimental preparations assessing the role of context in these interference paradigms is reminiscent of similar phenomena in rats with hippocampal inactivation or lesions.…”
Section: Discussionmentioning
confidence: 97%
“…The magnitude of a conditioned taste aversion (CTA) can be modulated by a change in the time of day between conditioning and test (Manrique, Gámiz, Morón, Ballesteros, & Gallo, 2009;Morón et al, 2002). This procedure shows that animals tested in temporal contexts different from that of the conditioning acquire less aversion, which is similar to what has been consistently described by changing the spatial context (Boakes, Elliot, Swinbourne, & Westbrook, 1997;Bonardi, Honey, & Hall, 1990;Bouton, 1993;Bouton, Westbrook, Corcoran, & Maren, 2006;González, Garcia-Burgos, & Hall, 2012;Pearce & Bouton, 2001;Rosas & Bouton 1997).…”
Section: Taste Stimulus Restriction Temporal Contextmentioning
confidence: 49%